Mpox Infection and Endocrine Health: Bridging the Knowledge Gap - Christos Savvidis; Manfredi Rizzo; Ioannis Ilias (Medicina)
Mpox (MPX), caused by the Monkeypox virus (MPXV), is a zoonotic orthopoxvirus infection with increasing global relevance due to sustained human-to-human transmission. While primarily known for cutaneous and systemic involvement, emerging evidence suggests that MPX may also disrupt endocrine function. This narrative review aims to synthesize current clinical, experimental, and epidemiological findings on MPX-related endocrine complications. We explore the potential impact of MPXV on the thyroid, adrenal glands, and gonads, and discuss the underlying mechanisms, clinical manifestations, and implications for patient management. MPX has been implicated in viral-induced subacute thyroiditis, with cases exhibiting thyrotoxicosis followed by hypothyroidism, likely mediated by direct viral infiltration or immune dysregulation. Additionally, MPX may contribute to adrenal insufficiency through viral invasion, immune-mediated destruction, or hypothalamic–pituitary–adrenal (HPA) axis dysfunction, exacerbating metabolic and inflammatory complications. MPXV’s persistence in testicular tissue raises concerns about reproductive health, with potential implications for fertility, hormone production, and viral transmission. The virus may also modulate host steroid pathways through interactions with glucocorticoid, androgen, and estrogen receptors, influencing immune responses and disease severity. Given these findings, clinicians should maintain vigilance for endocrine dysfunction in MPX patients, particularly in immunocompromised individuals. The role of steroid therapy in MPX remains complex, requiring careful balancing of its anti-inflammatory benefits against potential risks of viral persistence and immune suppression. Further research is essential to clarify MPX’s endocrine impact and optimize management strategies.